A "good death" with irreversible liver disease: Talking with patients and families about deteriorating health and dying. Issue 1 (28th July 2015) - Boyd, Kirsty; Kimbell, Barbara; Murray, Scott; Iredale, John
<x xml:space="preserve">Abstract</x> Watch a video presentation of this article Watch the interview with the author Answer questions and earn CME